ANALISIS HIDRAULIKA SISTEM POLDER MINI UNTUK PENANGANAN BANJIR DI BENGAWAN SOLO (Studi Kasus Wilayah Rawan Banjir Desa Sumbangtimun dan Desa Kandangan, Bojonegoro) - , Hanggar Ganara Mawandha ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Sumbangtimun and Kandangan villages in Bojonegoro district are the area that the most affected by flooding due to overflow of Bengawan Solo River. Losses due to flood were estimated to reach billion rupiah with the greatest losses from the agricultural sector. Based on the recommendation of BBWS Bengawan Solo in 2011, an embankment surrounding the flood prone area is required to prevent water overflowing from Bengawan Solo River which is known as polder system. Polder system that developed is a mini polder system where it covers small flood prone area. The research is aimed to develop a hydraulic flow modelling around the flood prone area, to determine the mini polder system design, to study water management in the mini polder area and to establish operational procedures of mini polder system accordingly. The hydraulic flow characteristics are modelled by HEC-RAS and Pondpack software. HEC-RAS is used to analyze the hydraulic flow along Bengawan Solo River while Pondpack is used to analyze the influence of local rainfall that causes flooding in the research area. According to the result of hydraulic modelling along the research area, the embankment of mini polder system is designed by the 2-yearly flood return period with its crest elevation at +18.5 m. The 2-yearly flood return period is used as basis to design the embankment because of low construction cost. Furthermore, the embankment design of mini polder system has to give the minimal impact of hydraulic alteration for the downstream area. To anticipate a greater flood design, the mini polder system is equipped with such a skotbalk that used as flood control gates. The flood control gates are opened when the water level reaches elevation at +18.2 m (crest elevation of flood control gates) or opened for leaching the farming land. In anticipation of flooding due to local rainfall, both retention pond and pumping system can be used. The retention pond without using pumping system needs the storage area of 32,092 m2 with the bottom elevation at +7.5 m, while using pumping system with the capacity of 6 m3/s the storage area becomes 32,322 m2 with the bottom elevation at +10 m. If the storage capacity is maintained in the existing condition then the required pumping capacity is larger than 12 m3/s. The flood-prone area is effectively saved by using mini polder system and losses due to 2-yearly flood return period could be avoided.